A simpler prescription to calculate MHV amplitudes for gravitons at tree level in superstring theory - Ursulino, Tiago Pinheiro [UNESP] (2013)
In this work we review the simple formulas found for MHV amplitudes of gluons and gravitons inside the contexts of super-Yang-Mills with supersymmetry N = 4 and supergravity with supersymmetry N = 8. We then review the prescription proposed by Berkovits and Maldacena [5] which simpli?es the calculation of those amplitudes for gluons inside the context of open superstrings, and which reproduces the correct results for 4 and 5 gluons, besides reducing to the sYM results in the 'alfa linha' = 0 limit, as veri?ed in [5] and [22]. Next, we extend the Berkovits-Maldacena prescription to the closed superstring, using it ?rst to calculate the MHV amplitude for 4 gravitons and verifying the result with the ones found in the literature by usual methods (result already obtained in [8]). As an original contribution to the subject, we will prove that, in the 'alfa linha' = 0 limit, the prescription gives the result of supergravity found by Hodges [17]